Hello stranger - Kleypas, Lisa (Kleypas, Lisa. Ravenels, 2018)
Dr. Garrett Gibson, England's only female physician, and Ethan Ransom, a former Scotland Yard detective with mysterious loyalties, share a one-night stand before becoming embroiled in a dangerous mission that is complicated by their growing feelings for one another.